Salvia palmetorum (Lamiaceae), a new species from Sonora, Mexico - Jesús Guadalupe González-Gallegos; Susan D. Carnahan (Revista Mexicana de Biodiversidad)
A new Salvia L. species was discovered in the vicinity of San Carlos Bay (Guaymas county) in Sonora, Mexico. The discovery was carried out during botanical explorations for the floristic inventory of the area. The new taxon is described and illustrated. This is an interesting addition to the Flora of Sonora because it constitutes the first Salvia endemic to this state. The species is characterized by an unusual combination of characters within Salvia subg. Calosphace (Benth.) Epling: densely white-tomentulose stems, presence of bracteoles, flowers arranged in thyrses, trimucronate upper calyx lip and ornate connective with an antrorse obtuse tooth. The taxon is also atypical among Mexican Salvia subg. Calosphace in growing in palm groves below 100 m elevation.